Nevanlinna characteristics of sequences of meromorphic functions and Julia’s exceptional functions - A. Ya. Khrystiyanyn; O. B. Khylynska; O. B. Khylynska (Математичні Студії, 2011)
Uniformly convergent sequences of meromorphic functions in the Caratheodory-Landau sense on annuli are considered. We prove that the sequences of their Nevanlinna type characteristics converge uniformly on intervals. The result is applied to the study of the Nevanlinna characteristics of Julia's exceptional functions.